2022
DOI: 10.2147/ijn.s338897
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Generating Amine-Functionalized Magnetic Nanoparticles Coupled with Carboxymethyl Chitosan for pH-Responsive Release of Doxorubicin

Abstract: Magnetic nanoparticles have been used in diverse pharmaceutical applications because they can potentially be used to target specific sites. In the present work, a new type of nanocomposites is designed as a carrier of controlled bioactive agent delivery. Methods: Amine-functionalized magnetic nanoparticles (amine-MNPs) are coupled with carboxymethyl chitosan (CMC) to generate the nanocomposites, namely MNPs-CMC, which can be further loaded with doxorubicin (DOX) to produce MNPs-CMC-DOX. The generated nanocompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…At class level, the number of clostridium in the model group was higher than that in the normal group, while the number of clostridium in the traditional Chinese medicine group was lower. Studies have shown that the colonization of clostridium intestinalis can effectively induce the production of IL-17 and IL-22 by CD4 helper T cells (namely 17 cells) in the lamina propria of the intestinal mucosa, and the more 17 cells detected in the lamina propria of the intestinal mucosa, the more clostridium colonized in the intestinal mucosa [17][18][19][20]. However, the intestinal tract with fewer 17 cells in the lamina propria lacks clostridium colonization.…”
Section: Related Workmentioning
confidence: 99%
“…At class level, the number of clostridium in the model group was higher than that in the normal group, while the number of clostridium in the traditional Chinese medicine group was lower. Studies have shown that the colonization of clostridium intestinalis can effectively induce the production of IL-17 and IL-22 by CD4 helper T cells (namely 17 cells) in the lamina propria of the intestinal mucosa, and the more 17 cells detected in the lamina propria of the intestinal mucosa, the more clostridium colonized in the intestinal mucosa [17][18][19][20]. However, the intestinal tract with fewer 17 cells in the lamina propria lacks clostridium colonization.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to being a unique technique for transporting zinc, zinc oxide nanoparticles (ZnO-NPs) have crucial implications in the treatment of a range of disorders, including diabetes [ 13 ]. Zinc supplementation has been demonstrated to have an ameliorative impact in preclinical investigations [ 13 , 14 ]. As a result, the development of a zinc-based medication for the treatment of diabetes and its complications might be promising [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Today, biopolymers are used in the different fields 6 , 47 , 52 56 . Among biopolymers, chitosan is an N -deacetylated type of chitin, found in nature, such as in Crabs, Shrimp, squid, etc.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). Chitosan (CS) is an abundant, biodegradable, hydrophilic, and natural polysaccharide, which affords desirable structural features for mechanical and chemical modifications 6 , 47 , 52 . It is an ideal support for the immobilization of metal nanoparticles due to its high stability, high surface area and low cost.…”
Section: Introductionmentioning
confidence: 99%